2019
DOI: 10.1002/adfm.201905694
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Modified Metallic Ti3C2Tx MXene as Electron Transport Layer for Planar Heterojunction Perovskite Solar Cells

Abstract: MXenes are a large and rapidly expanding family of two-dimensional (2D) materials which, owing to their unique optoelectronic properties and tunable surface termination, find a wide range of applications including energy storage and energy conversion. In this work, Ti3C2Tx MXene nanosheets are applied as a novel type of electron transport layer (ETL) in low-temperature processed planar-structured perovskite solar cells (PSCs). Interestingly, simple UV-ozone treatment of the metallic Ti3C2Tx that increases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 47 publications
1
100
0
Order By: Relevance
“…This effect was shown in the study of Liu et al,32 where MXenes have been used to reduce the Schottky barrier for electron injection with 2D semiconductors. In fact, MXenes have been successfully used in PSCs 20,21,33. Very recently a thorough study has shown that MXenes can be used to fine‐tune the band alignment between the perovskite layer and both the ETL and HTL, with a significant improvement of both J sc and V oc as well as the fill factor (FF), resulting in efficiencies that can be improved from 15% to above 20% 19…”
Section: Introductionmentioning
confidence: 99%
“…This effect was shown in the study of Liu et al,32 where MXenes have been used to reduce the Schottky barrier for electron injection with 2D semiconductors. In fact, MXenes have been successfully used in PSCs 20,21,33. Very recently a thorough study has shown that MXenes can be used to fine‐tune the band alignment between the perovskite layer and both the ETL and HTL, with a significant improvement of both J sc and V oc as well as the fill factor (FF), resulting in efficiencies that can be improved from 15% to above 20% 19…”
Section: Introductionmentioning
confidence: 99%
“…MXenes are a new family of 2D nanostructured materials originally reported in 2011. [ 23 ] The excellent electrochemical properties of MXenes make them widely applicable for electromagnetic interference shielding, [ 24–25 ] photodegradation, [ 26 ] photovoltaics, [ 27–28 ] electrochemical catalysis, [ 29 ] supercapacitors, and lithium ion batteries. [ 30–32 ] MXenes are prepared from MAX phases by etching the A layer (usually Al or Si) with a strong acid solution such as HF or LiF/HCl.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum time of UV‐ozone treatment can generate oxide‐like TiO bonds which facilitate electron transfer and reduce recombination at the interface. [ 134 ] Amorphous indium gallium zinc oxide (InGaZnO 4 ) was revisited as a new ETL for PSCs by Rao et al. and a PCE of 17.4% was obtained.…”
Section: Inorganic Etmsmentioning
confidence: 99%